KINERJA SEKTOR PERTANIAN DI PROVINSI JAWA TIMUR PADA MASA PANDEMI COVID-19 - Ines Paramithasari; Sri Widayanti; Nuriah Yuliati; Prasmita Dian Wijayati (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
The study was intended to analyze the position of the agricultural sector in the East Java Province of the covid-19 pandemic by determining the position of the agricultural sector at the time before the covid-19 pandemic and the covid-19 pandemic and identifying the factors that determined how the agriculture sector was performing. The collection of data on this study is secondary data obtained from the Statistical Center and the Indonesian Bank. The method of data analysis used is the Location Quotient analysis (LQ) and the Shift Share. This examination proposes that the situation of the agricultural sector at the time before the covid-19 pandemic was a non-base sector with an LQ value of 0,77. This occurs due to the conversion of agricultural land that is less in favor of the agricultural side even though East Java is one of the areas that has the largest agricultural production. At the time of the covid-19, the performance of the agricultural sector in East Java Province is a non-base sector with an LQ value of 0,79. This happened because of the Covid-19 pandemic which affected food security due to an unsupportive situation and prone to production problems. The rise in the value of LQ is expected to be better for agriculture sector performance. The factor that determines the performance of the agricultural sector is a factor of economic structure with a value of SSS greater than LSS.